Navigating the Green Finance Landscape: A Comprehensive Bibliometric Exploration of Current Trends, Evolution, and Prospects - Rizvi, Noor; Adil, Adil; Kapuria, Cheshta; Iqbal, Thahani; Malik, Sakshi (2023)
Climate change and sustainability have become global focal points, exemplified by the 2015 Paris Agreement. This has led to the emergence of "green finance," a term often intertwined with climate finance. Distinguishing between the two can be challenging, but both focus on financial mechanisms for addressing climate change and sustainability. This paper employs bibliometric analysis to provide insights into academic research on green finance. We find that green finance research is predominantly led by scholars from developed economies, with publications primarily appearing in policy and environmental journals rather than mainstream economics or finance journals. Our analysis suggests three future research directions: a finance-centric approach, research from developing countries' perspectives, and anticipation of emerging challenges in this policy-driven field. This study contributes to understanding the conceptual nuances and emerging trends in green finance research.